Surveillance of Bacterial Meningitis in the Italian Hospital of Desio: A Twenty-Year Retrospective Study - Jari Intra; Davide Carcione; Roberta Maria Sala; Claudia Siracusa; Paolo Brambilla; Valerio Leoni (Applied Microbiology, 2024)
Bacterial meningitis is a severe infection with a high fatality rate, and affects children in particular. Three vaccines against the most common bacterial causatives of meningitis, Haemophilus influenzae type b, Streptococcus pneumoniae, and Neisseria meningitides, exist. Monitoring the type and incidence of bacterial meningitis is important for making future prevention and control plans. In this study, we retrospectively analyzed data regarding bacterial meningitis recovered in the Italian Hospital of Desio from 2000 to 2019. Samples from a total of 128 patients were included. Streptococcus pneumoniae was the most common microorganism, isolated in 45 cases, followed by Neisseria meningitidis (14), Listeria monocytogenes (8), Streptococcus agalactiae (group B) (4), and Haemophilus influenzae type b (2). The implementation of vaccination schedules decreased the number of bacterial meningitis cases caused by H. influenzae type b, S. pneumoniae, and N. meningitidis. Considering the bacterial meningitis cases in subjects aged 0–12 years, no H. influenzae type b strain was isolated, five cases of N. meningitidis were identified before the introduction of vaccination, and seven S. pneumoniae strains were isolated before the introduction of the PCV13 vaccination. Surveillance studies allowed us to monitor changes in bacteria distribution and to guide vaccination strategies.